Carte réduite des bancs et de L'île de Terre-Neuve avec les Côtes du Golfe de St. Laurent et de L'Acadie - France. Dépôt des cartes et plans de la marine ([Paris], 1784)
Black and white. Prime meridian Paris. North arrows with rhumb lines. Depths indicated by soundings, with note. Table of latitudes and longitudes on which map is based, with notes. CNS map no. 115. - Leaf number in upper-right corner: No. 1 (Hyd. No. 57)